On the Mechanism of the Generation and Interannual Variations of the Summer Upwellings West and Southwest Off the Hainan Island. Issue 11 (19th November 2018) - Li, Yineng; Peng, Shiqiu; Wang, Jia; Yan, Jing; Huang, Hu
Abstract: The generation and interannual variations of the upwellings west and southwest off the Hainan Island (hereafter denoted as UWHI and USWHI, respectively) detected from satellite‐derived sea surface temperature as well as the mechanism behind them are investigated using a 3‐D high‐resolution ocean model with a set of sensitivity experiments. The model is able to reproduce the upwellings with significant variations in the seasonal and interannual time scales. Results of sensitivity experiments show that the joint effect of tidal mixing and stratification is the main cause of the generation of both UWHI and USWHI in summer, and the offshore pattern of the upwelling centers is closely associated with that of high mixing rate centers where currents interact with steep bathymetry. In addition, the circulation changes induced by the joint effect of tidal mixing and stratification have significant impacts on the upwellings, especially on USWHI. For the interannual variations of both UWHI and USWHI, the changes of the along‐shore winds, the tidal mixing, and the boundary currents are the main causes of the variations; the weak tidal mixing, enhanced along‐shore winds, and strong boundary currents result in the weakest upwellings there in 1998, with the enhanced along‐shore wind being the largest contributor. Plain Language Summary: Based on the numerical results, the joint effect of tidal mixing and stratification is the main cause of the generation of both the upwellings west and southwest off the Hainan Island. In addition, the weak tidal mixing, enhanced along‐shore winds, and strong boundary currents result in the weakest upwellings there in 1998, with the enhanced along‐shore wind being the largest contributor. Key Points: The joint effect of tidal mixing and stratification is essential to the upwelling generation west and southwest off the Hainan Island With tides included, currents induced by the baroclinic pressure gradient are the main drivers of the cold water uplifting The winds, the tides, and the boundary currents are the main causes of upwelling variations, with the winds being the largest contributor